PENGARUH DISIPLIN BELAJAR, GAYA MENGAJAR GURU, MINAT BELAJAR, DAN MOTIVASI BELAJAR TERHADAP KEAKTIFAN BELAJAR SISWA SMK CERSA PASAMAN - Intan Sari; Joliani; Yesmira Syamra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of learning discipline, teacher teaching style, learning interest, and learning motivation on student learning activity at SMK Cersa Pasaman. The type of quantitative research with descriptive and associative methods. The sampling technique used is the total sampling technique. Data were collected by questionnaire. Based on the results of the data analysis, it was obtained: 1) Learning discipline has a significant effect on learning interest. 2) Teacher teaching style has a significant effect on learning interest. 3) Learning discipline has a significant effect on learning motivation. 4) Teacher teaching style has a significant effect on learning motivation. 5) Learning discipline has a significant effect on learning activity. 6) Teacher teaching style has a significant effect on learning activity. 7) Learning interest has a significant effect on learning activity. 8) Learning motivation has a significant effect on learning activity. Based on the study, it was concluded that learning discipline, teacher teaching style, learning interest, and learning motivation on student learning activity at SMK Cersa Pasaman Barat had an effect.